The strong coupling constants of doubly heavy baryons with heavy mesons - Xiao-Hui Hu; Quan-Yu Zhou; Ye Xing; Yu-Ji Shi (European Physical Journal C: Particles and Fields)
Abstract In experiments, only one doubly charmed baryon $$Ξ _{cc}^{++}$$ Ξ cc + + has been successfully identified to date. The LHCb collaboration is poised to discover other doubly heavy baryons, $$Ξ _{cc}^{+}$$ Ξ cc + and $$Ξ _{bc}^{+}$$ Ξ bc + , necessitating a comprehensive study of doubly heavy baryons from various perspectives. Such investigations will elucidate the properties of the newly discovered states and facilitate the search for other doubly heavy baryons as predicted in the quark model. In this paper, we explore the strong coupling between the doubly heavy baryon, singly heavy baryon, and heavy meson, $$\mathcal{B}_{QQ^{′ }}\mathcal{B}_{Q}M_{Q^{′ }}$$ B Q Q ′ B Q M Q ′ , using the light-cone QCD sum rules approach. We analytically and numerically calculate the strong coupling, $$\mathcal{B}_{QQ^{′ }}\mathcal{B}_{Q}M_{Q^{′ }}$$ B Q Q ′ B Q M Q ′ , utilizing the light-cone distribution amplitudes of the singly heavy baryon $$\mathcal{B}_{Q}$$ B Q . Numerical predictions for these strong couplings are provided, along with an error analysis. Our theoretical findings can be employed to examine the strong and weak decay dynamics of doubly heavy baryons. Furthermore, our results may offer experimentalists a valuable tool for analyzing data on the strong coupling constants among hadronic multiplets.